(untitled) (Historia, 2021)
Stock-theft in the Conquered Territory during the 19th century. Little research has thus far been done on the role of stock-theft in the history of South African agriculture. This can be attributed, inter alia, to the fact that theft relates to negative interpersonal or intergroup relations as well as the sensitive and complex question of guilt. Some writers state in this regard that too much emphasis should not be placed on stock-theft in the analysis of border communities. They are of the opinion that claims to the same land were actually the ""fundamental basis of the conflict"". This article stresses the fact that during the 19th century stock-theft was indeed one of the most serious problems facing the agrarian community of the so-called Conquered Territory in the Eastern Free State border region. Cattle stealing was caused or facilitated by a host of factors, while the nature of the thefts and the way in which it was committed sheds some light on its seriousness. Although the extent of stock-theft can by no means be precisely calculated and losses cannot be quantified in exact financial terms, it becomes clear in this study that those who had to contend with it almost daily, regarded their position as intolerable, desperate and even hopeless. The continuous thefts, in fact, paralysed stock-farmers and filled them with a sense of insecurity, because in time it also caused their farms to diminish in value. Apart from its socio-economic implications stock-theft also had a negative effect on interstate relations since, together with border violations and squatting, it constituted the quintessence of the 19th century border issue between the Free State and Basutoland.